2016
DOI: 10.14202/vetworld.2016.299-303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different antioxidant additives in semen diluent on cryopreservability (−196°C) of buffalo semen

Abstract: Aim:The aim of this study was to evaluate the effect of different antioxidant additives in standard tris-fructose-egg yolk-glycerol (TFYG) extender on the cryopreservability of buffalo semen.Materials and Methods:Semen collection using artificial vagina, twice weekly for 5 weeks from three pedigreed health breeding bulls of Mehsani breed, aged between 6 and 8 years. Immediately after initial evaluation all 30 qualifying ejaculates (10/bull) were split into three aliquots and diluted at 34°C keeping the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Also, antioxidants properties of NAC can reduce the semen viscosity that important for improving the fertility and pregnancy rate (Verit et al, 2009). According to the fact, GSH production was affected by NAC treatment as a source of L-cysteine (Rushworth and Megson, 2014), it is clear to note that the significant improvement in spermatozoa characteristics in E4 (NAC) compared to control (E1) was in relation with the roles of NAC as ROS scavenger (Patel et al, 2016;Koohestanidehaghi et al, 2020) and cell apoptosis preserver (Dhouib et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Also, antioxidants properties of NAC can reduce the semen viscosity that important for improving the fertility and pregnancy rate (Verit et al, 2009). According to the fact, GSH production was affected by NAC treatment as a source of L-cysteine (Rushworth and Megson, 2014), it is clear to note that the significant improvement in spermatozoa characteristics in E4 (NAC) compared to control (E1) was in relation with the roles of NAC as ROS scavenger (Patel et al, 2016;Koohestanidehaghi et al, 2020) and cell apoptosis preserver (Dhouib et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…All this amounts to spermatozoon lesions such as oxidative damage or apoptosis, which can lead to negative results during the AI process [7]. Research has shown poor quality of keeping and freezability of buffalo semen [8,9]. Negative changes in buffalo spermatozoa are due to their unique physiology and higher polyunsaturated phospholipid levels in the plasma membrane [1], probably affecting the sperm motility, viability, acrosomal and DNA integrity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The motility and fertilization ability of spermatozoa can improve after addition of various motility enhancing agents or antioxidants [9,12]. The antioxidants check the chemical breakdown of the substrate resulting from oxidation, neutralize the free radicals, and reduce the risk of damage to spermatozoa during cryopreservation [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations